2010
DOI: 10.1093/beheco/arq054
|View full text |Cite
|
Sign up to set email alerts
|

Immune system activation affects song and territorial defense

Abstract: Previous studies have demonstrated that bird song is influenced by infection. We investigated how mounting an immune response by mountain white-crowned sparrows (Zonotrichia leucophrys oriantha) affects specific aspects of territorial song and behavior. We used song playback to simulate a territorial intrusion and elicit baseline song and behavioral responses. Individuals were then either injected with a saline control or with a lipopolysaccharide (LPS) solution to induce an acute immune response, and posttrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Previous studies find that poor environmental conditions or illness can reduce T-mediated reproductive or competitive behaviour in some avian species [43,44]. In these studies, lower T was associated with avoiding territorial behaviour that could induce a fight; thus facilitating avoidance of dangerous conflicts when an individual is in poor condition.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies find that poor environmental conditions or illness can reduce T-mediated reproductive or competitive behaviour in some avian species [43,44]. In these studies, lower T was associated with avoiding territorial behaviour that could induce a fight; thus facilitating avoidance of dangerous conflicts when an individual is in poor condition.…”
Section: Discussionmentioning
confidence: 84%
“…We performed one observation session of 45-60 min per day per aviary between 0900 h and 1300 h 1 day before immunization, and, respectively, 1, 2 and 4 days after immunization. Indeed, it is known that the inflammation caused by LPS can affect birdsong also 24 h after the challenge (Owen- Munoz et al 2010). Overall song rate was defined as the proportion of samples during which a male was singing (in any and all locations) compared to the total number of samples.…”
Section: Behavioural Observationsmentioning
confidence: 99%
“…Avian song represents a good example in this respect, and several studies have reported an association between the condition of the immune system and song expression (Saino et al 1997;Møller et al 2000;Garamszegi et al 2004). More specifically, it has been shown that an immune activation can negatively affect song performance (Owen- Munoz et al 2010;Lopes et al 2012). For example, Munoz et al (2010) reported that white-crowned sparrows (Zonotrichia leucophrys oriantha, Oberholser, 1932) decreased their singing output and shifted their vocal performances from a structured song to a more simple alarm call when the immune system was activated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations